The first Stages of Development of Pre-Islamic Poetry and its Main Focus (مجلة الواحات للبحوث والدراسات, 2025)
The hypothesis driving this study aimed to challenge the prevailing approach that marginalized pre-Islamic poetry from the temporal axis and overlooked its influence on human consciousness. Thus, the study sought to trace the evolution of pre-Islamic poetry across a significant two-hundred-year period, shedding light on its central themes. Findings indicate that pre-Islamic poetry underwent transformations reflecting the journey from existence to death, and back to existence, intertwining themes of life and social responsibility towards others. Keywords: pre-Islamic poetry, stillness, movement, existence, self-pity.